Forensic Science and Legal Medicine A Multidisciplinary Puzzle! - Sessa, Francesco (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Even if the terms "forensic sciences" and "legal medicine" seem to be synonymous, they could be defined as two sides of the same coin. It has been demonstrated that they are different components of the application of medical knowledge upon the legal system. Legal medicine has greater relevance to civil and tort law, impacting upon patient care, whereas forensic medicine relates to criminal law and damage to (or by) patients. This Special Issue, entitled "Forensic Science and Legal Medicine: A Multidisciplinary Puzzle!", collected accurate and up-to-date scientific information on all aspects of this theme, publishing original investigations, case series and case reports, and reviews in all forensic and medico-legal branches.